Differential effectiveness, efficiency, and acceptability of drill‐based interventions targeting multiplication facts - Adams, Sarah R.; Maki, Kathrin E. (Psychology in the schools, 2023)
Math facts are foundational for later math skill development, but many students demonstrate difficulties with math facts in early schooling. Drill‐based interventions have been shown to effectively target foundational academic skills; however, there is limited research examining drill‐based interventions for teaching math facts compared to basic reading skills. The purpose of this study was to compare the effects of incremental rehearsal (IR), traditional drill (TD), and strategic incremental rehearsal (SIR) on multiplication fact retention, fluency, and maintenance outcomes with 36 fourth and fifth graders. The study also examined intervention efficiency and treatment acceptability. Results showed no differences in retention, maintenance, or treatment acceptability across the interventions. There were significant differences in fluency at posttest, with IR resulting in the greatest fluency scores. Furthermore, TD was the most efficient intervention overall. Implications for practice and future research are also discussed. Practitioner points Incremental rehearsal was most effective for improving multiplication fact fluency. Traditional drill was the most efficient multiplication fact fluency intervention. Participating students reported similar levels of acceptability of all multiplication fact interventions.